2008
DOI: 10.1111/j.1440-1584.2008.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical location and sunburn in Queensland adults

Abstract: The rate of melanoma diagnosis in Queensland is higher than than in any other geographical location in the world. 1 In turn, geographical areas outside of major metropolitan regions in Australia have an increased number of excess deaths as a result of melanoma compared with metropolitan areas. 2 The higher number of excess deaths (difference in actual deaths in an area/ number of deaths in metropolitan areas) caused by melanoma in non-metropolitan areas 2 may be the result of these populations being exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…We were also unable to collect data on the rural or urban nature of the different district. This would be important given a significant body of evidence demonstrates greater UV exposure in rural compared to urban areas [35][36][37], hence the seasonality of TB might be more pronounced in rural regions. Lastly, we only included smear-positive pulmonary TB patients in this study, hence the results are not applicable to all forms of pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…We were also unable to collect data on the rural or urban nature of the different district. This would be important given a significant body of evidence demonstrates greater UV exposure in rural compared to urban areas [35][36][37], hence the seasonality of TB might be more pronounced in rural regions. Lastly, we only included smear-positive pulmonary TB patients in this study, hence the results are not applicable to all forms of pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…7 Differences in sun behavior have also been observed in Australian adolescents and adults according to their residential area (questionnaire/diary method, telephone interviews). 8,9 Rural adolescents were less likely than adolescents in the city to spent time in the sun during the weekend. 8 Rural adults were more likely to be sunburnt than adults in the city.…”
Section: Introductionmentioning
confidence: 99%
“…8 Rural adults were more likely to be sunburnt than adults in the city. 9 As children's sun behavior and exposure are of high relevance for later skin carcinogenesis, 10 we examined whether children's sun related behavior and UVR exposure differed according to their residential area (urban, suburban, rural). Sun-related behavior was recorded in diaries and UVR exposure was objectively measured by personal dosimetry during a summer season.…”
Section: Introductionmentioning
confidence: 99%
“…It was emphasized the need for additional preventive efforts and resources for individuals residing in non-metropolitan areas. 33 An examination of the literature revealed that, although outdoor workers, farmers and gardeners face greater risk of skin cancer, the rates of sun avoidance and use of sunscreen products among these group remain extremely low. 29,32,34 As a result of their literature review in Australia, Smit-Kroner and Brumby (2015) concluded that farmers use very limited to almost no sun protection.…”
Section: Discussionmentioning
confidence: 99%